Some Reflections On The Historical Significance Of The Activities Of Mahmudhoja Behbudi - Ahmadov Sabriddin; Mamataliyeva Surayyo Bobomuratovna (Procedia of Social Sciences and Humanities, 2022)
This article provides information about the activities of a prominent figure of the Jadid movement in Central Asia, Mahmudhoja Behbudi, in public and political life. Opinions will be expressed about the activities of Behbudi to popularize science and education in society, his work in this direction, his invaluable contribution to the development of culture and education, theater, etc.